Effective Mechanical Advantage About the Ankle Joint and the Effect of Achilles Tendon Curvature During Toe-Walking - Harkness-Armstrong, Carla; Debelle, Héloïse A.; Maganaris, Constantinos N.; Walton, Roger; Wright, David M.; Bass, Alfie; Baltzopoulos, Vasilios; O’Brien, Thomas D. (Frontiers in Physiology, 2020)
Aim: To study the causes of locomotor dysfunction, estimate muscle forces, or understand the influence of altered sarcomere and muscle properties and behaviours on whole body function, it is necessary to examine the leverage with which contractile forces operate. At the ankle joint, current methods to quantify this leverage for the plantarflexors do not account for curvature of the Achilles tendon, and so may not be appropriate when studying equinus gait. Thus, novel methodologies need to be developed and implemented to quantify the Achilles tendon moment arm length during locomotion. Methods: Plantarflexor internal moment arm length and effective mechanical advantage of 11 typically developed young adults were calculated throughout stance, while heel-toe walking and voluntarily toe-walking on an instrumented treadmill. Achilles tendon moment arm was defined in two ways: (1) assuming a straight tendon, defined between the gastrocnemius medialis myotendinous junction and Achilles tendon insertion point, and (2) accounting for tendon curvature, by tracking the initial path of the Achilles tendon from the calcaneal insertion. Results: When accounting for tendon curvature, Achilles tendon moment arm length and plantarflexor effective mechanical advantage did not differ between walking conditions (p > 0.05). In contrast, when assuming a straight tendon, Achilles tendon moment arm length (p = 0.043) and plantarflexor effective mechanical advantage (p = 0.007) were significantly greater when voluntary toe-walking than heel-toe walking in late stance. Discussion: Assuming a straight Achilles tendon led to a greater Achilles tendon moment arm length and plantarflexor effective mechanical advantage during late stance, compared to accounting for tendon curvature. Consequently, plantarflexor muscle force would appear smaller when assuming a straight tendon. This could lead to erroneous interpretations of muscular function and fascicle force-length-velocity behaviour in vivo, and potentially inappropriate and ineffective clinical interventions for equinus gait.